Denial of Pain Medication by Health Care Providers Predicts In-Hospital Illicit Drug Use among Individuals who Use Illicit Drugs. (2015) - Ti, Lianping; Voon, Pauline; Dobrer, Sabina; Montaner, Julio; Wood, Evan; Kerr, Thomas
Abstract : BACKGROUND: Undertreated pain is common among people who use illicit drugs (PWUD), and can often reflect the reluctance of health care providers to provide pain medication to individuals with substance use disorders. OBJECTIVE: To investigate the relationship between having ever been denied pain medication by a health care provider and having ever reported using illicit drugs in hospital. METHODS: Data were derived from participants enrolled in two Canadian prospective cohort studies between December 2012 and May 2013. Using bivariable and multivariable logistic regression analyses, the relationship between having ever been denied pain medication by a health care provider and having ever reported using illicit drugs in hospital was examined. RESULTS: Among 1053 PWUD who had experienced ≥1 hospitalization, 452 (44%) reported having ever used illicit drugs while in hospital and 491 (48%) reported having ever been denied pain medication. In a multivariable model adjusted for confounders, having been denied pain medication was positively associated with having used illicit drugs in hospital (adjusted OR 1.46 [95% CI 1.14 to 1.88]). CONCLUSIONS: The results of the present study suggest that the denial of pain medication is associated with the use of illicit drugs while hospitalized. These findings raise questions about how to appropriately manage addiction and pain among PWUD and indicate the potential role that harm reduction programs may play in hospital settings.